2012
DOI: 10.1097/mcc.0b013e328359fd57
|View full text |Cite
|
Sign up to set email alerts
|

Damage control orthopedics

Abstract: In severely injured patients, DCO should be considered. On the other hand, there is still a lack of randomized studies for a more precise characterization of the patients who benefit from DCO treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 19 publications
(13 reference statements)
0
24
0
6
Order By: Relevance
“…It was also found that ETC in polytraumatized patients with major blood loss may increase significantly the severity of this inflammatory response (SIRS) as described by various authors [2,3,5,7,8]. The development of this hyper-inflammatory reaction is manifested by activation of the immune system which triggers increased secretion of pro-inflammatory cytokines, such as interleukin-6 (IL-6) and IL-8 [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also found that ETC in polytraumatized patients with major blood loss may increase significantly the severity of this inflammatory response (SIRS) as described by various authors [2,3,5,7,8]. The development of this hyper-inflammatory reaction is manifested by activation of the immune system which triggers increased secretion of pro-inflammatory cytokines, such as interleukin-6 (IL-6) and IL-8 [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing research interest has been focused on the issue of cytokines and their role in immune activity in trauma patients [1][2][3][4][5]. Skeletal and tissue injuries may cause a hyper-inflammatory reaction of the immune system manifested by elevation in levels of pro-inflammatory cytokines and may lead to the development of systemic inflammatory reaction syndrome (SIRS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 From this emerged the philosophy of "damage control". 5 Thus, the priority of surgical interventions, and the time to perform them, were dependent on the patient's physiological state. 6 In the field of orthopedics, these concepts have been well understood for the management of long bone and pelvic fractures in polytraumatized patients.…”
Section: Introductionmentioning
confidence: 99%